Pelatihan kebugaran jasmani untuk menurunkan tingkat disfungsi seksual non-organik pada isteri =Physical Fitness Training to Decrease the Degree of Non-organic Sexual Dysfunction on Wives - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1995)
Like many other body processes, when sexual function goes along smoothly, it is usually taken for granted and given little thought. When sexual function is a problem in one way or another, however, it can be a source of anxiety, anguish and frustration that often leads to general unhappiness and digress in couples' relationships. The aim of this study is to check the effectiveness of physical fitness training to decrease the degrees of nonorganic sexual dysfunction on wives. Twelve married women voluntarily participated in the study. They were randomly assigned to experimental group or control group. Each group had 6 members. The experimental group was asked to practice the physical fitness training in 50 minutes per period, 3 times a week for 4 weeks. The degrees of non-organic sexual dysfunction, physical fitness and pulse rate were measured 3 times in the pre training, post training and 8 weeks after training as follow-up, to evaluate the effectiveness of training. Results indicated that the degrees of nonorganic sexual dysfunction in both gratips before training were relatively equal. It meant that these groups were on the same baseline. The degrees of nonorganic sexual dysfunction decreased significantly after training and 8 weeks after in the experimental group compared to the control group. This shows that physical fitness is effective to reduce the degrees of nonorganic sexual dysfunction, by providing a temporary respite from life stress. Physical fitneess may serve a beneficial restorative function that allows people to deal effectively with nonorganic sexual dySfunction circumstances.